Coexisting Phases of Individual VO2 Nanoparticles for Multilevel Nanoscale Memory - Kepič, Peter; Horák, Michal; Kabát, Jiří; Hájek, Martin; Konečná, Andrea; Šikola, Tomáš; Ligmajer, Filip (ACS nano, 2025)
Vanadium dioxide (VO2) has received significant interest in the context of nanophotonic metamaterials and memories owing to its reversible insulator-metal transition associated with significant changes in its optical and electronic properties. The phase transition of VO2 has been extensively studied for several decades, and the ways how to control its hysteresis characteristics relevant for memory applications have significantly improved. However, the hysteresis dynamics and stability of coexisting phases during the transition have not been studied on the level of individual single-crystal VO2 nanoparticles (NPs), although they represent the fundamental component of ordinary polycrystalline films and can also act like nanoscale memory units on their own. Here, employing transmission electron microscopy techniques, we investigate phase transitions of single VO2 NPs in real time. Our analysis reveals the statistical distribution of the transition temperature and steepness and how they differ during forward (heating) and backward (cooling) transitions. We evaluate the stability of coexisting phases in individual NPs and prove the persistent multilevel memory at near room temperatures using only a few VO2 NPs. Our findings unveil the physical mechanisms that govern the hysteresis of VO2 at the nanoscale and establish VO2 NPs as a promising component of optoelectronic and memory devices with enhanced functionalities.
Keywords: phase-change memory; hysteresis; coexisting phases; nanophotonics; vanadium dioxide; insulator−metal transition; transmission electron microscopy